Corn Silage Cost-Return Budget in Northeast Kansas - Lubben, Bradley D. (My University, 2000)
This publication contains information for a projected budged reflecting expected income and cost based on typical corn silage production practices in the northeast region of Kansas.
MF2364_2000_10
Keywords: MF2364; Economics; Crops; MF